Analysis of the Mursalah Issue: Legalized Contraception Devices Among Teenagers (Study of Article 103 Paragraph (4) Letter of Government Regulation Number 28 Of 2024) - Putri Handayani; Pendi Hasibuan; Hilma Daiatul Haqqi; Filda Rosa; Suci Surgani Putri (Fakultas Agama Islam Universitas Muhammadiyah Sumatera Barat, 2026)
This study analyzes contraceptive use among adolescents based on the principle of maslahah mursalah. The main focus is on opening Article 103 Paragraph (4) Letter e of Government Regulation Number 28 of 2024, which provides access to contraception for adolescents to support reproductive health. Through the maslahah mursalah approach, this study assesses the potential benefits and challenges of this policy, including its impact on cultural and religious values. The findings indicate that although the policy aims to reduce health and social risks, its implementation requires strict supervision and comprehensive education to ensure the fulfillment of moral and religious values.